Narrative Voices and Social Discourse in Trópico, by Marcos Carías Reyes - Venegas Vásquez, David Ernesto (2026)
This study offers a narratological and semiotic analysis of Trópico (1971), a novel by Marcos Carías Reyes, structured into three chapters: "Green Gold," "Silver Hill," and "The Mad Wind." Across these sections, its narrative voices (heterodiegetic and autodiegetic), together with their multiple focalizations and instances of metalepsis, operate as forms of narrative transgression that, through both individual and collective consciousness, configure the novel as an allegorical text denouncing the historical events that marked early twentieth-century Honduras. Building upon this premise, the study examines the narrative voices and temporal structure in light of the theories developed by Mieke Bal and Gérard Genette. The social and historical conflicts fictionalized in the novel are interpreted as an unstable mode of enunciation that disrupts narrative linearity and transforms the work into an aesthetic representation of the Honduran social crisis. In this way, Trópico establishes a poetics of fragmentation and memory, positioning itself within the Honduran literary avant-garde.